The Application of 2k Factorial Design to Determine the Luminance in Truck Parking Lots - Kandananond Karin (Transport and Telecommunication)
Road freight is a main mode of transportation in the logistics system, and its operation substantially depends on the heavy goods vehicle (HGV) trucks. One of the places, where trucks drivers spend hours in the long-haul route, is the parking lot. As a result, the safety matter in truck parking lots is important to the efficient performance of trucks in the system, especially during the night time. The enough amount of light significantly contributes to the safety of both drivers and pedestrians in the parking lots. This research focused on the optimal design of lighting installation in the target truck parking lot. The first stage of this study was the survey of the available truck parking lots, and the layout of the selected lot was used as the input of the simulation program. Afterwards, DIALux software was used to simulate the luminance for the chosen layout. To carry out the empirical study, a statistical design method, 2k full factorial design, was utilised to determine the relationship between design parameters and two responses, average luminance (Lav) and overall uniformity ratio (Uo). The design parameters were categorized into three groups, luminaire (LED wattage), the placement of pole (spacing, height, boom angle, and overhang), and pavement reflectance (average luminance factor or Q0). The analysis results showed that all designed parameters had a significant effect on Lav. There were also effects from two interactions, height*Q0 and boom angle*Q0. Moreover, Uo was considerably influenced by all parameters except wattage. Another important finding was that the following setting, spacing (low) and Q0 (high), should lead to the maximization of Lav and Uo. Finally, the validation stage was carried out by applying the optimal setting with the lighting design on a different truck parking layout. The empirical and validation results signified that the setting of design parameters for the highest Lav also led to the acceptable level of Uo as well. In practice, the research results can assist lighting designers to improve the design of a lighting system, so it would provide the adequate amount of light for truck parking lots.